Hospital readmissions following catheter ablation for atrial fibrillation with THERMOCOOL™ STSF/ THERMOCOOL™ ST catheter with CARTO™ 3 system versus TactiCath™ catheter with EnSite™ system - Alexandru I Costea; Rahul Khanna; Maximiliano Iglesias; Yiran Rong (Journal of Comparative Effectiveness Research)
Aim: Radiofrequency (RF) catheter ablation (CA) is a mainstay treatment for atrial fibrillation (AF). RF catheters with contact force (CF) sensing technology and electroanatomical mapping systems enable real-time assessment of catheter tip-tissue interface CF, facilitating individualized and precise CA. This study examined inpatient hospital readmissions in patients with AF treated with THERMOCOOL™ ST/ THERMOCOOL™ STSF catheter with the CARTO™ 3 System versus TactiCath™ catheter with the EnSite™ System. Materials & methods: Patients undergoing CA for AF between 1 July 2019 to 30 November 2021 were identified from the Premier Healthcare Database and grouped based on use of THERMOCOOL ST/STSF or TactiCath™. Study outcomes were all-cause, cardiovascular (CV)-, and AF-related inpatient readmission at 91–365-day post-CA. Inverse probability of treatment weighting of propensity scores balanced baseline patient, comorbidity and hospital characteristics. A weighted generalized estimating equation (GEE) model examined differences in readmission outcomes. Results: A total of 15,518 patients met inclusion criteria (THERMOCOOL ST/STSF, n = 13,001; TactiCath™, n = 2517). Patient characteristics were generally well-balanced after weighting. Patients treated with THERMOCOOL ST/STSF + CARTO 3 had a 20% lower likelihood of all-cause inpatient readmissions (7.8 vs 9.3%, chi-square p = 0.041; odds ratio [OR]: 0.80, 95% confidence interval [CI]: 0.66–0.96, GEE p = 0.019) and a 21% lower likelihood of CV-related inpatient readmission (5.2 vs 6.2%, chi-square p = 0.133, OR: 0.79, 95% CI: 0.62–0.99, GEE p = 0.043) in 91–365-days post-CA versus those treated with TactiCath™ + Ensite. No significant differences were observed for AF-related readmissions. Conclusion: Patients undergoing CA for AF treated with THERMOCOOL ST/STSF + CARTO 3 had a significantly lower risk of all-cause and CV-related inpatient hospital readmission versus those treated with TactiCath™ + Ensite.